A GENERALIZED NET MODEL OF COMMAND AND CONTROL SYSTEM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The relevance of the topic is related to the search for ways to support management in the military field by improving the command and control system (C2-system) of the armed forces. The purpose of the paper is to present an original generalized net model (GN-model) of a command and control system for the needs of the armed forces, including three main elements - personnel, structure and equipment, procedures. Through the integration of these three elements in the created GN-model to provide an opportunity for more detailed testing of different implementation options of the C2-system, even before its implementation in the process of managing the armed forces. To verify the GN-model, a simulation was performed in the GN IDE simulation environment and some results are presented. Some possible applications of the GN-model for the analysis and improvement of the C2-system of the armed forces are described.